2009
DOI: 10.1038/nchem.416
|View full text |Cite
|
Sign up to set email alerts
|

Complete chiral symmetry breaking of an amino acid derivative directed by circularly polarized light

Abstract: Complete chiral symmetry breaking of an amino acid derivative directed by circularly polarized light Noorduin, Wim L.; Bode, Arno A.C.; Meijden, Maarten van

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
176
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(181 citation statements)
references
References 18 publications
4
176
0
1
Order By: Relevance
“…Effect of UV circularly polarized light in space (gas phase or ices) has been suggested as an alternative way to induce excesses observed [34]. This hypothesis is being tested by laboratory experiments [35][36][37] but the source of the CPL at the vicinity of the early solar system still needs to be assessed. Chirality has been suggested to also occur in the IOM [38] and in hydroxy acids [39].…”
Section: Diversity Of Organic Compounds In Meteoritesmentioning
confidence: 99%
“…Effect of UV circularly polarized light in space (gas phase or ices) has been suggested as an alternative way to induce excesses observed [34]. This hypothesis is being tested by laboratory experiments [35][36][37] but the source of the CPL at the vicinity of the early solar system still needs to be assessed. Chirality has been suggested to also occur in the IOM [38] and in hydroxy acids [39].…”
Section: Diversity Of Organic Compounds In Meteoritesmentioning
confidence: 99%
“…Note that in this case the external field selects a spiral with the same chirality as its own, which is consistent with the chiral selection controlled by chiral fields in other systems. [30][31][32][41][42][43] However, the opposite chirality (CW) spiral wave can also be selected without changing the chirality of the CPEF. This scenario is illustrated in Fig.…”
Section: A Chiral Selection Of a Spiral Pairmentioning
confidence: 99%
“…[30][31][32][39][40][41][42][43] Over the past decades, chiral symmetry breaking induced by such chiral fields has received considerable interests from many scientific disciplines. [30][31][32][41][42][43] Different from spontaneous chiral symmetry breaking where the chiral selection is unpredicted, it was demonstrated that chiral fields not only cause the breaking of chirality but also could select a desired chirality, [30][31][32][41][42][43] which is closely related with that of the applied field. As an example, the chirality of a supramolecular structure can be selected by the vortex motion and depends on the chirality of the vortex.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, chiral symmetry breaking induced by such chiral fields has received considerable interests from many scientific disciplines [30][31][32][41][42][43] . Different from spontaneous chiral symmetry breaking where the chiral selection is unpredicted, it was demonstrated that chiral fields not only cause the breaking of chirality but also could select a desired chirality [30][31][32][41][42][43] , which is closely related with that of the applied field. As an example, the chirality of a supramolecular structure can be selected by the vortex motion and depends on the chirality of the vortex 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Possibly, one of the most interesting results caused by chiral fields or forces is chiral symmetry breaking, an ubiquitously observed scenario in nature [30][31][32][39][40][41][42][43] . Over the past decades, chiral symmetry breaking induced by such chiral fields has received considerable interests from many scientific disciplines [30][31][32][41][42][43] .…”
Section: Introductionmentioning
confidence: 99%